Mixed Signals: interpreting mixing patterns of different soil bioturbation processes through luminescence and numerical modelling - W. M. van der Meij; S. Riedesel; S. Riedesel; T. Reimann (SOIL)
Soil bioturbation plays a key role in soil functions such as carbon and nutrient cycling. Despite its importance, fundamental knowledge on how different organisms and processes impact the rates and patterns of soil mixing during bioturbation is lacking. However, this information is essential for understanding the effects of bioturbation in present-day soil functions and on long-term soil evolution.